Hethitisches Wörterbuch. Bd. III/2: Ḫ/ḫe- bis ḫu-, Lieferung 21 - Friedrich, Johannes (2012)
Herausgegeben von Albertine Hagenbuchner-Dresel mit Paola Cotticelli Kurras, Federico Giusfredi, Joost Hazenbos, Inge Hoffmann, Walther Sallaberger, unter Mitarbeit von Michael Frotscher, Amir Gilan, Mauro Giorgieri, Detlev Groddek, Alwin Kloekhorst, Jared L. Miller, Alfredo Rizzi, Hanna Roszkowska-Mutschler, Tobias Scheucher, Ingo Schrakamp, Michaela Zinko-Ofitsch.